Complaint Management and Channel Choice: An Analysis of Customer Perceptions - Garding, Stefan (Springer, 2015)
This book investigates customer perceptions and expectations of complaint channels. In addition to the conventional channels, the adequacy of online social networks as new complaint channel is analysed. The managerial recommendations to improve customer satisfaction are based on a survey and reveal critical determinants of customer channel choice and their expectation and perception of each complaint channel.